Inklusivitas Tata Kelola Kota Layak Anak di Kota Malang - Hermawan, Romy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The Child-Friendly City (CFC) initiative aims to promote children’s well-being. Malang City has implemented the CFC program and received multiple awards for its efforts. However, public access to information on CFC-related literacy remains limited. This study analyzes the inclusiveness of CFC governance in Malang City using UNICEF's inclusive Good Governance indicators through a descriptive qualitative method. The findings reveal that Malang's CFC meets the required indicators, with evident participation from the government, private sector, media, NGOs, and the community. Nonetheless, challenges persist, including child marriage, malnutrition, and suboptimal use of children’s forums. These issues result from weak coordination and collaboration among institutions and stakeholders, highlighting the need for broader involvement to enhance the program’s effectiveness.